Classification of library resources by subject on the library website: is there an optimal number of subject labels? - Miles MJ; Bergstrom SJ (Information Technology & Libraries, 2009)
The number of labels used to organize resources by subject varies greatly among library websites. Some librarians choose very short lists of labels while other choose much longer lists. We conducted a study with 120 students and staff to try to answer the following question: What is the effect of the number of labels in a list on response time to research questions? What we found is that response time increases gradually as the number of the items in the list grow until the list size reaches approximately fifty items. At that point, response time increases significantly. No association between response time and relevance was found.